Multiplexed droplet loop-mediated isothermal amplification with scorpion-shaped probes and fluorescence microscopic counting for digital quantification of virus RNAs. Issue 24 (21st May 2021) - Tan, Ya-Ling; Huang, A-Qian; Tang, Li-Juan; Jiang, Jian-Hui
Abstract : The development of multiplexed dLAMP with scorpion-shaped probes and fluorescence microscopic counting affords simultaneous digital quantification of multiple virus RNAs. Abstract : Highly sensitive digital nucleic acid techniques are of great significance for the prevention and control of epidemic diseases. Here we report the development of multiplexed droplet loop-mediated isothermal amplification (multiplexed dLAMP) with scorpion-shaped probes (SPs) and fluorescence microscopic counting for simultaneous quantification of multiple targets. A set of target-specific fluorescence-activable SPs are designed, which allows establishment of a novel multiplexed LAMP strategy for simultaneous detection of multiple cDNA targets. The digital multiplexed LAMP assay is thus developed by implementing the LAMP reaction using a droplet microfluidic chip coupled to a droplet counting microwell chip. The droplet counting system allows rapid and accurate counting of the numbers of total droplets and the positive droplets by collecting multi-color fluorescence images of the droplets in a microwell. The multiplexed dLAMP assay was successfully demonstrated for the quantification of HCV and HIV cDNA with high precision and detection limits as low as 4 copies per reaction. We also verified its potential for simultaneous digital assay of HCV and HIV RNA in clinical plasma samples. This multiplexed dLAMP technique can afford a useful platform for highly sensitive and specific detection of nucleic acids of viruses and other pathogens, enabling rapid diagnosis and prevention of infectious diseases.